Chlamydia psittaci infection-associated acute fibrinous and organizing pneumonitis: A case report - Xianhua Gui; Xiaohua Qiu; Yujuan Gao; Tingting Chen; Yuying Qiu; Jia Liu; Yonglong Xiao (IDCases)
Acute fibrinous and organizing pneumonia (AFOP) is a rare type of lung injury, and while Chlamydia psittaci pneumonia is a zoonotic disease, secondary AFOP has not been previously reported. We present a 53-year-old female with a 13-day history of cough, fever, and shortness of breath. High-resolution computed tomography (HRCT) showed multiple bilateral patchy shadows and consolidations in the left lung lower lobe. Empirical treatment was ineffective, and lung lesions worsened. Metagenomic next-generation sequencing (mNGS) confirmed Chlamydia psittaci infection. After minocycline treatment, the patient’s fever improved, but shortness of breath persisted. CT-guided lung biopsy revealed “fibrin balls” in the alveolar space and interstitial inflammatory infiltrates. Shortness of breath improved after glucocorticoid therapy, with significant lesion absorption noted on follow-up chest CT. This case suggests a possible association between AFOP and C. psittaci infection, supporting the use of combined antibiotic and glucocorticoid therapy.